2016
DOI: 10.1002/smll.201602363
|View full text |Cite
|
Sign up to set email alerts
|

5 nm Silver Nanoparticles Amplify Clinical Features of Atopic Dermatitis in Mice by Activating Mast Cells

Abstract: The triggering effect of silver nanoparticles (NPs) on the induction of allergic reactions is evaluated, by studying the activation of mast cells and the clinical features of atopic dermatitis in a mouse model. Granule release is induced in RBL-2H3 mast cells by 5 nm, but not 100 nm silver NPs. Increases in the levels of reactive oxygen species (hydrogen peroxide and mitochondrial superoxide) and intracellular Ca in mast cells are induced by 5 nm silver NPs. In a mouse model of atopic dermatitis induced by a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 57 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…Pulit et al (2011) cited that the contact of humans with AgNPs may cause adverse effects, and these different results may have been due to the different composition and thickness of the skin of small ruminants and humans. Another aspect to be considered is the size of the AgNPs, since Kang et al (2017) described that 5 nm AgNPs amplify the clinical features of atopic dermatitis, and Park et al (2011) found that 4 nm AgNPs presented a higher cytotoxic effect than AgNPs at high concentrations with 20 and 70 nm sizes. The AgNPs studied herein have an average size of 28 nm, and this characteristic can then be associated with a lower occurrence of adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Pulit et al (2011) cited that the contact of humans with AgNPs may cause adverse effects, and these different results may have been due to the different composition and thickness of the skin of small ruminants and humans. Another aspect to be considered is the size of the AgNPs, since Kang et al (2017) described that 5 nm AgNPs amplify the clinical features of atopic dermatitis, and Park et al (2011) found that 4 nm AgNPs presented a higher cytotoxic effect than AgNPs at high concentrations with 20 and 70 nm sizes. The AgNPs studied herein have an average size of 28 nm, and this characteristic can then be associated with a lower occurrence of adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Aluminum nanoparticles (AlNP), AuNP, FeNP, and SiNP have all been shown to modify DC antigen cross-presentation capacity (Blank et al 2011; Li et al 2011; Hirai et al 2012; Jiménez-Periáñez et al 2013; Kang S et al 2017; Mou et al 2017; Dong et al 2018). The mecha-nism of antigen uptake by DC is known to influence the preferential association of antigens with MHC I or II molecules.…”
Section: Metal Nanomaterials and Dermal Hypersensitivitymentioning
confidence: 99%
“…This effect was shown to be more pronounced with decreasing size with respect to AgNP and SiO 2 NP, but not for TiO 2 NP (Yanagisawa et al 2009; Hirai et al 2012b; Hirai et al 2015). Exposure to 5 nm AgNP during sensitization was associated with an augmentation of mast cell activity that resulted in more severe skin lesions that appeared earlier than those induced by 100 nm AgNP (Kang H et al 2017). Decreases in SiO 2 NP size were also associated with enhanced T H 2 responses, as evidenced by increased thymic stromal lymphopoeitin (TSLP) and IL-18 production (Hirai et al 2012b).…”
Section: Metal Nanomaterials and Dermal Hypersensitivitymentioning
confidence: 99%
“…Despite their hope and promises, nanotechnology-based solution can have also triggering effect on the induction of allergic reactions and the clinical amplification of such symptoms. Utilizing a mouse model, Kang and collaborators [86] found that 5- but not 100-nm nano-sized Ag-NPs induce release of granule from tryptase-positive mast cells, as well as lead to increased reactive oxygen species (ROS, hydrogen peroxide and mitochondrial superoxide) levels and intracellular calcium concentrations.…”
Section: Nanotechnology and Atopic Dermatitis: Current Challengesmentioning
confidence: 99%